Utilization of urea and expression profiles of related genes in the dinoflagellate Prorocentrum donghaiense. - Xiaoli Jing; Senjie Lin; Huan Zhang; Claudia Koerting; Zhigang Yu (PLoS ONE, 2017)
Urea has been shown to contribute more than half of total nitrogen (N) required by phytoplankton in some estuaries and coastal waters and to provide a substantial portion of the N demand for many harmful algal blooms (HABs) of dinoflagellates. In this study, we investigated the physiological and transcriptional responses in Prorocentrum donghaiense to changes in nitrate and urea availability. We found that this species could efficiently utilize urea as sole N source and achieve comparable growth rate and photosynthesis capability as it did under nitrate. These physiological parameters were markedly lower in cultures grown under nitrate- or urea-limited conditions. P. donghaiense N content was similarly low under nitrate- or urea-limited culture condition, but was markedly higher under urea-replete condition than under nitrate-replete condition. Carbon (C) content was consistently elevated under N-limited condition. Consequently, the C:N ratio was as high as 21:1 under nitrate- or urea-limitation, but 7:1 under urea-replete condition and 9:1 to 10:1 under nitrate-replete condition. Using quantitative reverse transcription PCR, we investigated the expression pattern for four genes involved in N transport and assimilation. The results indicated that genes encoding nitrate transport, urea hydrolysis, and nickel transporter gene were sensitive to changes in general N nutrient availability whereas the urea transporter gene responded much more strongly to changes in urea concentration. Taken together, our study shows the high bioavailability of urea, its impact on C:N stoichiometry, and the sensitivity of urea transporter gene expression to urea availability.